2014
DOI: 10.1080/01635581.2014.894099
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Apigenin, a Plant Flavonoid, for Imatinib-Sensitive and Resistant Chronic Myeloid Leukemia Cells

Abstract: Despite the presence of many therapeutic regimens like imatinib and other tyrosine kinase inhibitors, the development of resistance, intolerance, and side effects makes chronic myeloid leukemia (CML) therapy challenging. Thus, there is a need to discover novel drugs for CML patients. In this study, we attempted to assess apigenin, a common plant dietary flavonoid, in terms of its cytotoxic, apoptotic, and cytostatic effects on imatinib-sensitive and resistant Philadelphia-positive CML cells. We analyzed apigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Interestingly, apigenin itself inhibited cell growth because of its ability to induce cell cycle arrest at S and G2/M phases. In line with this, apigenin has been previously reported to inhibit cell proliferation and induces cell cycle arrest in various cell types [ 30 33 ].…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, apigenin itself inhibited cell growth because of its ability to induce cell cycle arrest at S and G2/M phases. In line with this, apigenin has been previously reported to inhibit cell proliferation and induces cell cycle arrest in various cell types [ 30 33 ].…”
Section: Discussionmentioning
confidence: 61%
“…And in an oral squamous cell carcinoma cell line SCC-25, apigenin treatment caused cell cycle arrest at both G0/G1 and G2/M checkpoints, associated with decreased expression of cyclin D1 and E, and inactivation of CDK1 [ 33 ]. Interestingly, Solmaz et al reported that apigenin exposure induced G2/M arrest in imatinib-sensitive K562 cells while arresting imatinib-resistant K562/IMA3 cells in S phase especially at 100 μM apigenin [ 34 ]. Taken together, those data suggest that apigenin possibly modulates cell cycle progression in a dose-dependent and/or cell line specific manner.…”
Section: Apigenin In Cancer Therapymentioning
confidence: 99%
“…[301] K562 and K562/IMA3 cell lines The study concluded that apigenin inhibits cell proliferation and induces apoptosis by upregulating the activity of caspase-3 and arresting the cells in G2/M phase of cell cycle repectively. [302] Myeloma cell lines U266 and RPMI 8226 Apigenin was found to kill MM cells by targeting the trinity of CK2-Cdc37-Hsp90. By depleting these kinases, apigenin suppresses both constitutive and inducible activation of STAT3, ERK, AKT and NF-кB.…”
Section: S Nomentioning
confidence: 99%